GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI PENGARUH PROFITABILITAS PADA PRAKTIK PERATAAN LABA - Herlina, Herlina; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi, 2016)
Companies that practice income smoothing will be able to control the excess rate of profit when the company announced laba.Tujuan this study was to determine the good corporate governance as a moderating influence on the profitability of income smoothing practices. This study was performed on companies listed in the Indonesia Stock Exchange (BEI) and included in the ranking of corporate governance perception index (CGPI) 2010-2014. Samples are taken as much as six companies, with non-probability sampling method with purposive sampling technique. Data collection method used was non-participant observation and data analysis technique used is the descriptive analysis, logistic regression analysis (logistic regression) and Moderating Regression Analysis (MRA). Based on the analysis found that the profitability of simultaneous significant negative effect on income smoothing practices by GCG as a moderating influence that reinforces negative relationship profitability in income smoothing practices.
Keywords: Good Corporate Governance, Profitability, Gain Flattening Practice.